FDI and Job Creation in China - Sune Karlsson; Nannan Lundin; Fredrik Sjöholm; Ping He (Research Institute of Industrial Economics (IFN), 2007)
This paper examines the effect of FDI on job creation in the Chinese manufacturing sector. As one of the worlds largest recipients of FDI, China has arguably benefited from foreign multinational enterprises in various respects. However, one of the main challenges for China, and other developing countries, is job-creation, and the effect of FDI on job creation is uncertain. The effect depends on the amount of jobs created within foreign firms as well as the effect of FDI on job creation in domestic firms. We analyze FDI and job creation in China using a large sample of manufacturing firms for the period 1998-2004. Our results show that FDI has positive effects on employment growth. The positive effect of job creation in foreign firms is associated with their firm characteristics and, in particular, their access to export markets. There also seems to be a positive indirect effect on job creation in domestically owned firms, presumably caused by spillovers.
Keywords: F23; J21; J23; 330; China; Employment; Foreign Direct Investment; Job Creation; Direktinvestition; Beschäftigungseffekt; Verarbeitendes Gewerbe; China